Development of a Web-Based Information System to Digitalize Florist SME Operations - Marlinda Marlinda; Khusnul Khotimah (bit-Tech, 2025)
Small and medium enterprises (SMEs) often face inefficiencies due to manual business processes that result in data redundancy, high error rates, and delayed service delivery. Queen Flower Shop in North Lampung exemplifies these challenges, as it continues to record transactions and inventory manually, reducing productivity and decision-making accuracy. This study addresses this problem by developing a web-based information system designed to digitalize florist operations and enhance overall business performance. The system was developed using the Waterfall model, comprising five sequential stages—requirements analysis, design, implementation, testing, and maintenance. Implemented through the CodeIgniter 4 framework based on the Model–View–Controller (MVC) architecture and supported by a MySQL database, the system integrates modules for user authentication, product management, online ordering, and automated reporting. Black-box testing validated that all features operated as expected, achieving a 100% success rate. Quantitatively, system implementation reduced average transaction processing time by approximately 45% and eliminated recurring data duplication errors. These outcomes demonstrate that the developed system significantly improves operational efficiency, data accuracy, and user satisfaction while ensuring modularity and scalability for future enhancements. The study contributes a practical and replicable model for SME digitalization, particularly in the creative and retail sectors, promoting transparency, competitiveness, and long-term sustainability in the digital economy.